Qinggan Yipi capsule ameliorates hepatic fibrosis in rats by down-regulating the TGF-β1/Smad2/3 signaling pathway and improving gut microbiota imbalance - Wenjing Xue; Haiqing Liu; Ziheng Su; Siqi Wang; Junping Cheng; Yunzhi Pan; Lurong Zhang (Frontiers in Pharmacology)
Background and objectiveQinggan Yipi Capsule (QgYp) is a hospital preparation that has been used for many years in the treatment of chronic liver diseases. However, the mechanism of QgYp in ameliorating hepatic fibrosis (HF) remains unclear. This study aims to clarify the anti-liver fibrosis effect of QgYp and its mechanism of action.MethodsThis study uses a carbon tetrachloride (CCl4) induced HF rat model and TGF-β1 stimulated HSC-T6 cell line (rat HSCs) as experimental models. The therapeutic effects were evaluated through pathology, biochemical tests, and ELISA. The therapeutic mechanism of QgYp for HF was predicted through network pharmacology. The expression of TGF-β1/Smad2/3 related proteins was detected by qPCR analysis and Western blot analysis. The composition of the gut microbiota was analyzed using 16S rRNA gene sequencing.ResultsHistopathological analysis, serum biochemical tests, and ELISA measurements showed that QgYp effectively decreased the levels of ALT, AST, HA, LN, PCIII, and IV-C while improving collagen deposition and hepatocyte necrosis. Protein-protein interaction (PPI) network analysis screened HF-related genes, including peroxisome proliferator-activated receptor gamma (PPARG), tumor necrosis factor (TNF), and TGF-β1. GO and KEGG analyses indicated that QgYp significantly affects TGF-β signaling pathway. In addition, the results of qPCR and Western blot analysis from both in vitro and in vivo experiments indicated that QgYp significantly downregulated the expression of proteins and mRNA associated with the TGF-β1/Smad2/3 pathway. The 16S rDNA gene sequencing results showed that QgYp can increase the diversity and richness of the gut microbiota in HF rats and alter the composition of the gut microbiota.ConclusionQgYp could effectively ameliorate HF, and this effect might be connected to the downregulation of the TGF-β1/Smad2/3 pathway, the suppression of HSCs activation, and regulation of gut microbiota dysbiosis.